Metabolic Modulation of Macrophage Function Post Myocardial Infarction - Zhao, Mingyue; Wang, Dennis Ding-Hwa; Liu, Xiaojing; Tian, Rong (Frontiers in Physiology, 2020)
Macrophages are key components of the innate immunity, and they play critical roles in heart health and diseases. Following acute myocardial infarction (MI), infiltrating macrophages undergo drastic phenotypic transition from pro-inflammatory in the early stage to pro-healing in the late stage. Transcriptome analyses of macrophage in the infarct zone shows a time-dependent reprogramming of mitochondrial and metabolic function which parallels the changes of macrophage function. These observations suggest that mitochondrial and metabolic targets could be exploited for therapeutic opportunities. In this article, we reviewed the recent work on immunometabolic features of macrophage over the MI time continuum. In addition, we summarized currently proposed mitochondrial pathways involved in the functional polarization of macrophage, and discussed their potential relevance to the outcome of MI. We expect that these findings will stimulate further investigations in metabolic modulation of innate immunity in the post-MI setting, which could ultimately lead to new strategies for therapy.